Geopolitical consequences of the escalation of the Ukrainian crisis - Proroković, Dušan (Sociološki pregled, 2022)
The armed conflict in Ukraine, which began in February 2022, also has its own geopolitical dimension. The hypothesis that is being proven in this paper is: The consequences of the escalation of the Ukrainian crisis irreversibly transform the geopolitical environment and thus induce the formation of a new world order. The aim of the research is to look at the trends in the transformation of the geopolitical environment and, accordingly, to analyze the potential scenarios for the development of international relations. The research is based on the theory of structural realism and classical geopolitical theory, and the study is carried out using the methods of analysis, synthesis, content analysis and geopolitical pattern on the dichotomy of the thalassocratic and tellurocratic concepts.